An integrated approach to judicial decision making: the death penalty in South Africa - Franks, Stephenie E. (2003)
Existing judicial research has firmly established the role of the law and the courts in the political system of the United States. Yet very little systematic empirical research has been conducted to fully explore the extent to which theories of judicial behavior based upon the American judicial system are applicable to other legal systems. As a result, these theories lack generalizability and, moreover, have failed to determine if the U.S. judiciary is comparable to other court systems or simply an anomaly within a broader comparative framework. Given this void within the existing literature, this study extends several theories of judicial behavior developed in the American context to South Africa’s highest court, the Appellate Division, throughout the time period 1950-1990—roughly the rise and fall of apartheid. Specifically, it employs an integrated approach derived from both the legal and extralegal approaches of judicial decision making to a particularly salient issue area, the death penalty, and discovers that ideology and race—rather than legal factors—are perhaps the strongest predictors of death penalty decisions. The implications of these findings are that judicial decision making is much more complex than what the legal model suggests and, concomitantly, that theories of judicial behavior extrapolated from the American context are capable of similarly determining the degree to which politics plays a role within the legal system of South Africa